The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jocd.12866
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and possible mechanisms of botulinum toxin treatment of oily skin

Abstract: Background:Oily skin is one of the most common dermatological complaints. Oily skin may be accompanied by enlarged pores, acne, and seborrheic dermatitis.Moreover, oily skin has negative effects on self-perception. Most therapeutic approaches used to treat oily skin have had varying degrees of efficacy and include topical treatments, such as photodynamic therapy and lasers. However, certain of these therapies for oily skin may lead to severe side effects. With the expanding use and high safety profile of botul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 24 publications
0
60
0
2
Order By: Relevance
“…No standardized approaches nor agents have proven effective for the treatment of seborrhea. Current available treatments that can reduce sebum include topical drugs, systemic treatments, botulinum toxin injection, and phototherapy . Exact mechanisms of action of some treatments are still unclear, but various mechanisms have been proposed, with ultimate outcomes being sebosuppression via reducing sebocyte proliferation, differentiation, and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…No standardized approaches nor agents have proven effective for the treatment of seborrhea. Current available treatments that can reduce sebum include topical drugs, systemic treatments, botulinum toxin injection, and phototherapy . Exact mechanisms of action of some treatments are still unclear, but various mechanisms have been proposed, with ultimate outcomes being sebosuppression via reducing sebocyte proliferation, differentiation, and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…5 More recently, intradermal injection of BTX has been used off-label for various aesthetic conditions, including facial skin laxity, excess sebum production, and enlarged facial pores. [8][9][10][11][12][13] These effects could be attributed to the paralysis of arrector pili muscles or decreased sebum production via acetylcholine inhibition. 10,13,14 However, previous studies relied on subjective evaluation and lacked long-term clinical data.…”
mentioning
confidence: 99%
“…Intradermal injection of botulinum toxin is suggested as a new strategy for treating excessive sebum and enlarged pores . Rose et al reported that botulinum toxin treatment decreases sebum production to 80% after 1 month, which is comparable with the reported sebum reduction by oral isotretinoin (60%‐90%) .…”
Section: Management Recommendationsmentioning
confidence: 73%
“…It is usually accompanied by enlarged pores, acne, and seborrheic dermatitis. Moreover, oily skin has negative effects on self‐perception . Meanwhile, sensitive skin is described as a condition of subjective hyper‐reactivity to exogenous factors.…”
Section: Introductionmentioning
confidence: 99%